2019
DOI: 10.3389/fphar.2019.00329
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Discovery of the Potential Toxic Compounds in Polygonum multiflorum by UHPLC/Q-Orbitrap-MS-Based Metabolomics and Correlation Analysis

Abstract: The dry roots of Polygonum multiflorum (PM), involving both the raw and processed materials, are widely used as the traditional Chinese medicine for treating various diseases in China. Hepatotoxicity has been occasionally reported in patients who consume PM. Unfortunately, no definite criteria are currently available regarding the processing technology of PM for reduction the toxicity. In this work, we aimed to investigate the variations of PM metabolite profiles induced by different pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 42 publications
2
17
0
1
Order By: Relevance
“…The identification of the major constituents of the extracts was performed in the negative ionisation mode, which was found to contain a larger number of signals in contrast to the positive mode. Similar to other authors, anthraquinones and single phenolics were determined in the negative ionisation mode [24]. Only flavonoids were visible in both positive and negative ionisation modes, which was helpful in the identification of this group of secondary metabolites.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…The identification of the major constituents of the extracts was performed in the negative ionisation mode, which was found to contain a larger number of signals in contrast to the positive mode. Similar to other authors, anthraquinones and single phenolics were determined in the negative ionisation mode [24]. Only flavonoids were visible in both positive and negative ionisation modes, which was helpful in the identification of this group of secondary metabolites.…”
Section: Resultssupporting
confidence: 52%
“…Compared to other rhubarbs from the same genus, the heart-shaped rhubarb contains only small quantities of resveratrol and its derivatives. The authors identified trans- resveratrol and tetrahydroxystilbene- O -(acetyl)-hexose as the stilbene derivatives present in the extracts [24, 27]. Both compounds were traced in the roots and in the stems, and their quantity was close to the methods' limit of detection in the remaining organs.…”
Section: Resultsmentioning
confidence: 99%
“…According to the literature [9], the best processing technology for PMR process was to steam for 24h in order to eliminate the potential hepatotoxicity of PM. Further analysis was performed by focusing on the 45 samples of PMRP using the water steaming method, since this processing technology is the most commonly used and has been recommended by Chinese Pharmacopoeia.…”
Section: Quanti Cation Of 6 Dianthrones In 86 Batches Of Commercial Pmrpmentioning
confidence: 99%
“…The chemical composition of PMR can be signi cantly altered after processing, and then the hepatotoxicity of PMR can be minimized accordingly. Some studies have shown that the processing could result to a decrease of some compounds, such as 2, 3, 5, 4'-tetrahydroxystilbene-2-O-β-D-glucopyranoside (THSG), emodin-8-O-β-D-glucoside, catechin, epicatechin, and physcion-8-O-β-D-glucopyranoside, whereas these compounds did not disappear [2,[9][10]. These studies demonstrated that there may be no direct link between these compounds and PMRinduced liver injury.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with traditional research methods, this research method has more comprehensive and more efficient analysis results and plays a very good role in promoting basic research on the quality of traditional Chinese medicine. It has become a new trend and hot spot in the research of active ingredients of traditional Chinese medicine in recent years [14,15]. We used ultra-performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF-MS), an effective technique for the systematic analysis of complex metabolomes, to analyze and identify the chemical components of A. senticosus from different parts of the plant [16,17].…”
Section: Introductionmentioning
confidence: 99%